A review on the development of rock slope stability assessment in Malaysia - A. F., Salmanfarsi; Haryati, Awang; Mohamad Idris, Ali (IOP Publishing, 2019)
Rock mass classification systems are commonly used in the design and construction of rock engineering, and have seen widespread modifications and validations by various researchers over the last few decades. In Malaysia, several methods for large-and medium-scale slope assessment systems have been developed for prediction of landslide risk. Most of the methods however were found to be unsatisfactory in actual prediction of slope failures. The rock mass classification, in particular the slope mass rating (SMR), continues to be the preferred preliminary method in small-scale assessment of rock slope stability. Kinematic analysis is also widely used for predicting potential failure in structurally-controlled rock slope, and has been used independent or as compliment to rock mass classification systems. These methods are not entirely adequate in incorporating the local condition of rock mass: as a result, several works have modified the parameters of slope stability assessment methods to consider the condition of the rock mass such as the effect of heterogeneous rock units and weathering of rocks. In addition to these conventional methods, geophysical methods such as electrical resistivity, and remote sensing methods such as light detection and ranging (LiDAR), are increasingly being used in both preliminary and post-slope failure analysis. This paper reviews the development of rock slope stability assessment methods in Malaysia, as well as covering the viability of integrating geophysical and laser scanning methods with conventional methods to develop a more comprehensive rock slope assessment.